2020
DOI: 10.21203/rs.2.13863/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of an Oxygen Planar Optode to Assess the Effect of High Velocity Microsprays on Oxygen Penetration in a Human Dental Biofilms In-Vitro

Abstract: Background Dental plaque biofilms are the causative agents of caries, gingivitis and periodontitis. Both mechanical and chemical strategies are used in routine oral hygiene strategies to reduce plaque build-up. If allowed to mature biofilms can create anoxic microenvironments leading to communities which harbor pathogenic Gram-negative anaerobes. When subjected to high velocity fluid jets and sprays biofilms can be fluidized which disrupts the biofilm structure and allows the more efficient delivery of antimic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…After publication of the original article [ 1 ], the authors identified errors in the authors’ names of Sara R. Palmer and Rala D.P. Kandukuri.…”
mentioning
confidence: 99%
“…After publication of the original article [ 1 ], the authors identified errors in the authors’ names of Sara R. Palmer and Rala D.P. Kandukuri.…”
mentioning
confidence: 99%